2017
DOI: 10.1016/j.ekir.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery and Kidney-Related Outcomes

Abstract: The prevalence of severe obesity in both the general and the chronic kidney disease (CKD) populations continues to rise, with more than one-fifth of CKD patients in the United States having a body mass index of ≥35 kg/m2. Severe obesity has significant renal consequences, including increased risk of end-stage renal disease (ESRD) and nephrolithiasis. Bariatric surgery represents an effective method for achieving sustained weight loss, and evidence from randomized controlled trials suggests that bariatric surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 74 publications
(94 reference statements)
2
76
0
8
Order By: Relevance
“…Clinically desirable reduction of certain biochemical markers, such as creatinine, CRP, uric acid, ALT, AST, GGT, connected with renal and hepato-biliary function or inflammatory activity, was also observed in our study group, but values of these parameters remained in the normal ranges in the whole observation period. Other authors provide information that the overall long-term (above > 12 months) influence of bariatric treatment on kidney, liver and inflammatory function is positive, so these results could be considered as a good prognostic factor also in our assessment [39][40][41][42]. C-reactive protein and other inflammatory marker levels' postoperative increase is also proven to be diagnostic in operation technique related complications, such as bleeding or anastomosis leak [43], but the patients who developed such complications were excluded from the follow-up, and therefore mentioned conclusions on the postoperative inflammatory function could be stated.…”
Section: Niddm Arterial Hypertension Partial Remission (%)mentioning
confidence: 88%
“…Clinically desirable reduction of certain biochemical markers, such as creatinine, CRP, uric acid, ALT, AST, GGT, connected with renal and hepato-biliary function or inflammatory activity, was also observed in our study group, but values of these parameters remained in the normal ranges in the whole observation period. Other authors provide information that the overall long-term (above > 12 months) influence of bariatric treatment on kidney, liver and inflammatory function is positive, so these results could be considered as a good prognostic factor also in our assessment [39][40][41][42]. C-reactive protein and other inflammatory marker levels' postoperative increase is also proven to be diagnostic in operation technique related complications, such as bleeding or anastomosis leak [43], but the patients who developed such complications were excluded from the follow-up, and therefore mentioned conclusions on the postoperative inflammatory function could be stated.…”
Section: Niddm Arterial Hypertension Partial Remission (%)mentioning
confidence: 88%
“…Weight‐reduction therapy improves blood pressure, insulin resistance, dyslipidaemia, and obstructive sleep apnoea . A previous study's findings showed that compared with usual care, obese patients with type 2 diabetes benefitted more from bariatric surgery (BS), which included a lower incidence of nephropathy; however, the study was limited to patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Potential factors underlying the increased risks for CKD and ESRD include obesity-mediated hypertension, insulin resistance, obesity-related glomerulonephropathy, renin-angiotensinaldosterone system activation, inflammation, and dysregulated adipocytokine production. 5,6 Weight-reduction therapy improves blood pressure, 7 insulin resistance, dyslipidaemia, and obstructive sleep apnoea. 8 A previous study's findings showed that compared with usual care, obese patients with type 2 diabetes benefitted more from bariatric surgery (BS), which included a lower incidence of nephropathy 9 ; however, the study was limited to patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The mean serum levels of C cystatin was signi icantly greater in the postoperative group as compared to preopera-investigated and, in some studies, improvement of the glomerular iltration rate (GFR), reduction of hyper iltration and reduction of microalbuminuria can be observed, preventing the onset of CKD and its progression [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, there is no agreement on this issue [29].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, no statistically signi icant difference was observed in relation to the glomerular iltration rate when compared to the pre and post-bariatric surgery groups, corroborating other studies that do not evidence the effect of bariatric surgery on the improvement of renal function. On the other hand, some even suggest a worsening of the renal function after the surgical approach [28,29,40,41]. Thus, adding cystatin C for increasing sensitivity and speci icity for better use of renal function equations did not give evidence for supporting improvement of renal function after bariatric surgery in obese patients.…”
Section: Discussionmentioning
confidence: 98%